c-Abl Inhibitors in Parkinson’s: Exploring Hypotheses on Alpha-Synuclein Modulation - Jyutia Nargish; Hirok Jyoti Baishya; Piyong Sola (Advanced Pharmaceutical Bulletin)
Parkinson’s disease (PD) stands as the second most prevalent neurodegenerative disorder, impacting a global population estimated between 6 to 10 million individuals. The condition primarily arises from a dopamine deficiency and the presence of α-synuclein, forming Lewy bodies in the substantia nigra pars compacta (SNcp). Despite the ongoing quest to unravel the precise pathophysiological mechanisms underlying PD, recent literature reviews posit that heightened activation of the Abelson non-receptor tyrosine kinase(c-Abl), in brain tissues plays a pivotal role in neurodegeneration observed in PD patients. Notably, these studies put forth compelling evidence suggesting that c-Abl inhibitors’ interventions exhibit notable therapeutic potential. The potential benefits encompass enhancements in motor function, prevention of dopamine neuron loss, and the meticulous regulation of α-synuclein phosphorylation and clearance. These findings collectively advocate for the exploration of c-Abl as a prospective therapeutic target, thereby presenting inhibitors of this kinase as promising candidates for intervention in the management of PD.